2017
DOI: 10.1182/blood-2017-01-763003
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and outcomes of progression of CLL on the BCL2 inhibitor venetoclax

Abstract: Key Points• Complex karyotype and fludarabine refractoriness are key risk factors for progression of CLL on venetoclax.• Bruton tyrosine kinase inhibitors are active in patients with CLL after prior therapy with venetoclax.The BCL2 inhibitor venetoclax achieves responses in ∼79% of patients with relapsed or refractory chronic lymphocytic leukemia/small lymphocytic lymphoma (RR-CLL/SLL), irrespective of risk factors associated with poor response to chemoimmunotherapy. A limitation of this targeted therapy is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
156
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(161 citation statements)
references
References 24 publications
4
156
1
Order By: Relevance
“…reported that, in a group of heavily pretreated patients, 37% of patients progressed on venetoclax at a median follow up of 23 months, and that 8.2% of patients discontinued therapy due to other reasons with no patients discontinuing due to toxicity. 2 We also note these results differ from recent real world BCR inhibitor series where AEs were the most common reason for drug discontinuation, followed by CLL progression. 20 …”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…reported that, in a group of heavily pretreated patients, 37% of patients progressed on venetoclax at a median follow up of 23 months, and that 8.2% of patients discontinued therapy due to other reasons with no patients discontinuing due to toxicity. 2 We also note these results differ from recent real world BCR inhibitor series where AEs were the most common reason for drug discontinuation, followed by CLL progression. 20 …”
Section: Discussioncontrasting
confidence: 87%
“…Complex karyotype was not associated with inferior PFS, despite being shown to be a risk factor for progression in patients receiving venetoclax in a recent study by Anderson et al . 2 It is possible that our shorter follow up accounts for this discrepancy. Interestingly, del(11q) did not adversely affect PFS.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The mutation profile in patients with CLL is dynamic and complex and therefore it is of immense interest to understand the status of BTK mutations and mutational evolution patterns after discontinuation of BTKi therapy. Patients with disease progression often are treated with the Bcl‐2 inhibitor venetoclax . In the current study, we examined the mutation evolution in 3 patients with CLL with disease progression after discontinuation of BTKi therapy and treatment with venetoclax.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some in vitro studies have shown that EBV can transform CLL cells into an aggressive, clonally related DLBCL [27][28][29], others have suggested that, in CLL patients, EBV can transform normal bystander B lymphocytes into clonally unrelated DLBCL, particularly in those receiving immunosuppressive fludarabine, alkylating agents, or the anti-CD52 antibody alemtuzumab [26,[30][31][32][33][34]. More recently, several studies have reported that CLL patients with early progression under therapy with the novel agents ibrutinib, idelalisib and venetoclax can develop aggressive transformation to DLBCL (including EBV + cases), suggesting that these drugs can increase the risk of RT by permitting viral reactivation during therapy-related immunosuppression [35][36][37][38][39][40][41][42]. Because of this potentially devastating consequence, the role of EBV in the development of currently incurable EBV + DLBCL in CLL patients warrants urgent investigation, with the aim of developing strategies to monitor and prevent transformation and to define effective therapies.…”
Section: Introductionmentioning
confidence: 99%